Mad for solutions

Find all integers a , b , c a, b, c such that a 2 = b c + 1 a^2 = bc + 1 and b 2 = c a + 1 b^2 = ca + 1 .

Find the number of such triplets containing only integers.


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

We have that

a 2 b 2 = ( b c + 1 ) ( c a + 1 ) = c ( b a ) ( a b ) ( a + b ) = c ( a b ) a^{2} - b^{2} = (bc + 1) - (ca + 1) = c*(b - a) \Longrightarrow (a - b)(a + b) = -c*(a - b)

( a b ) ( a + b + c ) = 0. \Longrightarrow (a - b)(a + b + c) = 0.

So either (i) a b = 0 a - b = 0 or (ii) a + b + c = 0 a + b + c = 0 .

(i) If a b = 0 a = b a - b = 0 \Longrightarrow a = b then a 2 = c a + 1 c = a 2 1 a = a 1 a a^{2} = ca + 1 \Longrightarrow c = \dfrac{a^{2} - 1}{a} = a - \dfrac{1}{a} for a 0. a \ne 0.

(Note that a = b = 0 a = b = 0 is not a possible solution as the original equations would then both yield the absurdity 0 = 1 0 = 1 .)

In this case c c will be an integer only if a = 1 a = 1 or a = 1 a = -1 . The respective solution triplets ( a , b , c ) (a,b,c) are then ( 1 , 1 , 0 ) (1,1,0) and ( 1 , 1 , 0 ) (-1,-1,0) .

(ii) If a + b + c = 0 c = ( a + b ) a + b + c = 0 \Longrightarrow c = -(a + b) then a 2 = b c + 1 = b ( a + b ) + 1 a^{2} = bc + 1 = -b(a + b) + 1

a 2 + b a + b 2 1 = 0 a = b ± b 2 4 ( b 2 1 ) 2 = b ± 4 3 b 2 2 . \Longrightarrow a^{2} + ba + b^{2} - 1 = 0 \Longrightarrow a = \dfrac{-b \pm \sqrt{b^{2} - 4(b^{2} - 1)}}{2} = \dfrac{-b \pm \sqrt{4 - 3b^{2}}}{2}.

Now a a will be an integer only if 4 3 b 2 > 0 4 - 3b^{2} \gt 0 , which is only the case when b = 0 , ± 1 b = 0, \pm 1 .

When b = 0 b = 0 we have a = 0 ± 4 2 = ± 1 a = \dfrac{0 \pm\sqrt{4}}{2} = \pm 1 , yielding solution triplets ( 1 , 0 , 1 ) (1,0,-1) and ( 1 , 0 , 1 ) (-1,0,1) .

When b = 1 b = 1 we have a = 1 ± 4 3 2 = 0 , 1 a = \dfrac{-1 \pm \sqrt{4 - 3}}{2} = 0,-1 , yielding solution triplets ( 0 , 1 , 1 ) (0,1,-1) and ( 1 , 1 , 0 ) (-1,1,0) .

When b = 1 b = -1 we have a = 1 ± 4 3 2 = 1 , 0 a = \dfrac{1 \pm \sqrt{4 - 3}}{2} = 1,0 , yielding solution triplets ( 1 , 1 , 0 ) (1,-1,0) and ( 0 , 1 , 1 ) . (0,-1,1).

Having considered all possible cases, we see that the total number of desired solution triplets is 8 . \boxed{8}.

Nice detailed solution! Another way to think about (ii) is adding the two equations and obtain a 2 + b 2 + c 2 = 2 a^2+b^2+c^2=2 . Thus one of the squares is 0 0 and the rest are 1 1 . Keeping in mind that a + b + c = 0 a+b+c=0 , we know the solutions must be permutations of 0 , 1 , 1 {0,1,-1} , which gives 6 6 solutions.

Xuming Liang - 5 years, 5 months ago

Log in to reply

Thanks! I prefer your approach for case (ii); it's much more elegant than mine. :)

Brian Charlesworth - 5 years, 5 months ago
Patrick Corn
Jan 11, 2016

Solve for c c to get c = a 2 1 b = b 2 1 a c = \frac{a^2-1}{b} = \frac{b^2-1}{a} . So a 3 a = b 3 b a^3-a = b^3-b .

First: if a = b a = b , then we get a ( a c ) = 1 a(a-c) = 1 , so a = b = ± 1 a = b = \pm 1 . We'll come back to this case in a second.

Now look at a graph of the function y = x 3 x y = x^3-x . It's increasing and negative until ( 1 , 0 ) (-1,0) and increasing and positive after ( 1 , 0 ) (1,0) . The only horizontal line that passes through two points with integer x x -coordinate is x = 0 x = 0 , which passes through the points where x = 1 , 0 , 1 x = -1,0,1 . So if a b a \ne b , then a a and b b have to be in { 1 , 0 , 1 } \{ -1,0,1 \} .

So in either case a a and b b are in { 1 , 0 , 1 } \{ -1,0,1 \} . So there are nine potential solutions, and it's easy to compute that the only possibility that doesn't lead to a solution is a = b = 0 a = b = 0 . So there are 8 \fbox{8} solutions in all.

Prince Loomba
Jan 18, 2016

This question was in rmo 2015

Ansh Bhatt
Jan 10, 2016

a^2=bc+1

.•. (a+1)(a-1)=bc

Similarly, (b+1)(b-1)=ac

Dividing both the equations we get

[(a+1)(a-1)]/[(b+1)(b-1)]=b/a

.•. (a-1)(a)(a+1)=(b-1)(b)(b+1)

Here we get two cases

(i) a=b

Then,

a^2=bc+1

But since a=b

.•. a^2=ac+1

.•. c=(a^2-1)/a

Which will give you an integer only if a=1 or -1

Thus, we get two solutions (1,0,1) and (-1,0,-1)

(ii) a≠b

Then,

For (a-1)(a)(a+1)=(b-1)(b)(b+1)

To be true both quantities should have one multiplication by zero.

.•. taking

1) (a-1)=b=0

2) (a-1)=(b+1)=0

3) a=(b-1)=0

4) a=(b+1)=0

5) (a+1)=(b-1)=0

6) (a+1)=b=0

By these six cases we get the value of a and b. We can find c by substituting in original equation.

We get the six permutations of (-1,0,1).

Which give us a total of 8 solutions.

"For (a-1)(a)(a+1)=(b-1)(b)(b+1)

To be true both quantities should have one multiplication by zero."

I think this requires some more justification. (My solution indicates one way to do this.)

Patrick Corn - 5 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...